Raw Material as Indonesia’s Diplomatic Power in International Trade Towards the EU Case Study: Nickel Ban Policy - Meirizal, Ade; Juliana, Cindy; julia Putri, Dinda (Journal of World Trade Studies, 2022)
Based on the amendment to Law Number 3 of 2020, Indonesian authorities decided to launch a nickel ban policy on several countries, including the EU, at the beginning of 2021. Authorities claimed that the nickel ban policy can stimulate job creation at the domestic level, bring economic value and improve industry complexity in Indonesia. The EU assumes that nickel export restrictions implemented by Indonesia affect the vital industries in the EU, especially the stainless steel and battery industries. The EU took action to bring this case to the WTO Dispute Settlement Body (DSB). This paper analyzes how important raw materials can be utilized to achieve Indonesian national interest using a qualitative method, adding to the discussion of relations between power and interdependence in global trade, how power can apply in the dynamics of the Indonesian nickel ban policy, and bringing achievement in terms of Indonesia's national interest. The power game utilized by Indonesia is also analyzed in facing a major global economic power. Finally, this paper will examine raw materials (nickel matte) as a diplomatic power in the global market and how its policies bring instability to industries in the EU.